ACCULTURATION STRATEGIES IN JHUMPA LAHIRI'S WHEREABOUTS - Ankita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Jhumpa Lahiri’s Whereabouts is a deeply introspective novel that explores themes of solitude, identity, and cultural adaptation. Unlike her previous works, which focus on the immigrant experience in America, Whereabouts is set in an unnamed Italian city and features a protagonist who experiences a complex relationship with her surroundings. This paper examines the protagonist’s acculturation strategies using John Berry’s acculturation model, which categorizes adaptation strategies as integration, assimilation, separation, or marginalization. By analyzing the protagonist’s internal monologue and interactions, this study reveals how Lahiri presents acculturation as a psychological rather than merely a sociological process. The protagonist oscillates between marginalization and partial integration, unable to fully embrace or detach from her environment. Through her sparse prose, fragmented structure, and use of setting, Lahiri crafts a nuanced narrative that reflects the emotional toll of cultural ambiguity.